Efficacy of latissimus dorsi and teres major tendon transfer in anterosuperior irreparable rotator cuff tears and posterosuperior irreparable rotator cuff tears - Chang Hee Baek; Chaemoon Lim; Jung Gon Kim; Bo Taek Kim; Seung Jin Kim (Journal of Orthopaedic Surgery and Research)
Abstract Background There are various options of tendon transfer according to the different types of irreparable rotator cuff tears (IRCTs). However, there were no clear treatment options for the IRCTs involving the anterior, superior and posterior rotator cuff tears (global IRCTs). Latissimus dorsi and teres major (LDTM) could be transferred anteriorly or posteriorly in global IRCTs. The purpose of this study is to evaluate the efficacy of LDTM transfer in anterosuperior IRCTs (ASIRCTs) and posterosuperior IRCTs (PSIRCTs). Methods The patients who underwent anterior LDTM (aLDTM) transfer (aLDTM group, n = 35) for ASIRCTs or pLDTM transfer (aLDTM group, n = 33) for PSIRCTs between January 2017 and December 2020 were reviewed retrospectively. Clinical and functional outcomes were evaluated based on pain, patient-reported outcome scores, active range of motion (aROM) and strength of aROM. Radiological outcomes were evaluated using arthritic changes in the glenohumeral joint and transferred tendon integrity. Arthritic changes in the glenohumeral joint were evaluated using the acromiohumeral distance (AHD) and Hamada classification on the true anteroposterior radiograph. Results No significant intergroup difference was confirmed in patient demographics except for preoperative fat infiltration grade of subscapularis and infraspinatus. The postoperative Constant score, and University of California and Los Angeles (UCLA) score of aLDTM group were significantly higher than that of pLDTM group (p < 0.001 and < 0.001, respectively). Moreover, the achievement of minimal clinically important difference (MCID) for American Shoulder and Elbow Surgeons score and UCLA score showed a significant difference between two groups (p = 0.021 and 0.042, respectively). The postoperative forward elevation (FE) was significantly higher in aLDTM group (p = 0.046). The postoperative FE strength and abduction strength were significantly higher in aLDTM group (p = 0.001 and 0.025, respectively). Moreover, the mean improvement of internal rotation strength in aLDTM group was significantly higher than mean improvement of external rotation strength in pLDTM group (p = 0.011). The progression of arthritic change was significantly higher in pLDTM group (p = 0.002). Conclusion Although LDTM transfer is an effective and safe treatment option for ASIRCTs and PSIRCTs, LDTM transfer is more effective for ASIRCTs than PSIRCTs due to its biomechanical advantage and tendon transfer principles. Level of study Level III.